The Interaction of Traditional Values and Digital Culture: A Phenomenological Study of the Social Identity of Indonesia's Gen Z - Ketut Purwantoro; Diah Soelistyowati; Irma Winingsih (Universitas Teuku Umar, 2025)
The phenomenon of socio-cultural shifts in Indonesia in the digital era has become increasingly complex, particularly as Generation Z emerges as the main actor in the use of technology while simultaneously inheriting traditional values. This study aims to deeply understand the subjective experiences of Gen Z in integrating traditional values—such as mutual cooperation, politeness, and kinship—with digital cultural practices characterized by speed, individuality, and global connectivity. Using a phenomenological approach, this research explores how Indonesian Gen Z negotiates its social identity amid the dialectic between the continuity of local values and digital innovation. The findings reveal that traditional values still hold significant influence, accounting for approximately 45% to 55% in shaping digital interaction patterns, particularly in aspects of communication ethics, online community solidarity, and the expression of cultural identity on social media. Although digital culture presents challenges such as global homogenization and tendencies toward individualism, Gen Z tends to engage in a process of hybridization, adapting digital technologies without completely abandoning traditional roots. Thus, the social identity of Indonesian Gen Z is not constructed dichotomously but through dynamic interactions that produce new communication patterns while opening space for the reinterpretation of local values in a global context. This study underscores the importance of balancing digital modernity and traditional heritage in shaping the identity of the younger generation and contributes conceptually to the understanding of Indonesia's national identity amid the intensifying currents of globalization.